2010
DOI: 10.1186/1471-2288-10-1
|View full text |Cite|
|
Sign up to set email alerts
|

A tutorial on pilot studies: the what, why and how

Abstract: Pilot studies for phase III trials - which are comparative randomized trials designed to provide preliminary evidence on the clinical efficacy of a drug or intervention - are routinely performed in many clinical areas. Also commonly know as "feasibility" or "vanguard" studies, they are designed to assess the safety of treatment or interventions; to assess recruitment potential; to assess the feasibility of international collaboration or coordination for multicentre trials; to increase clinical experience with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
2,121
0
51

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,202 publications
(2,272 citation statements)
references
References 24 publications
16
2,121
0
51
Order By: Relevance
“…The main purpose of the follow up was to determine whether the outcomes could be assessed, and complete data was obtained on those followed up. Following guidance for feasibility studies 31, 32, 62, 63, 64, no formal statistical testing for effectiveness was carried out. Inspection of the data (Table 2) shows that men in the intervention group reduced the frequency of their binge drinking (8 or more units in a session) by slightly more than men in the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main purpose of the follow up was to determine whether the outcomes could be assessed, and complete data was obtained on those followed up. Following guidance for feasibility studies 31, 32, 62, 63, 64, no formal statistical testing for effectiveness was carried out. Inspection of the data (Table 2) shows that men in the intervention group reduced the frequency of their binge drinking (8 or more units in a session) by slightly more than men in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Following the guidance of methodologists 31, 62, 63, 64, this feasibility study did not attempt to estimate the effectiveness of the intervention. Feasibility studies are underpowered to detect intervention effects.…”
Section: Discussionmentioning
confidence: 99%
“…Although few pilot studies about feasibility of physical therapy in older adult have been found, the current literature shows the importance of this type of studies because they can contribute to avoid mistakes in the implementation of a RCT, especially when dealing with older adults. 27,28 With reference to the specific objectives of the pilot study, recruitment for the small sample in this pilot was achieved within the time frame. A larger trial would be necessary to recruit participants from other nursing homes to obtain a larger sample.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a total of 44 participants were considered to be adequate for this purpose, as stated in some publications that concern the implementation of pilot studies. [25][26][27] Statistical Analysis Recruitment, participation, adherence rates, and percentage of participants randomized were presented descriptively. Descriptive statistics were also calculated to describe baseline data.…”
Section: Sample Size Calculationmentioning
confidence: 99%
“…We used a pilot RCT design 186 to assess the likely benefits and harms of named nurse PC to allow inferences about the possible causal effects of our new intervention. The MRC framework 30 recommends RCTs early in the development and testing of complex interventions.…”
Section: Summary Of the Upbeat-uk Programmementioning
confidence: 99%